1990
DOI: 10.1083/jcb.111.6.2341
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutations associated with peroxisome-to-mitochondrion mistargeting of alanine/glyoxylate aminotransferase in primary hyperoxaluria type 1.

Abstract: Abstract.We have previously shown that in some patients with primary hyperoxaluria type 1 (PH1), disease is associated with mistargeting of the normally peroxisomal enzyme alanine/glyoxylate aminotransferase (AGT) to mitochondria (Danpure, C. J., P. J. Cooper, P. J. Wise, and P. R. Jennings. J. Cell Biol. 108:1345-1352. We have synthesized, amplified, cloned, and sequenced AGT eDNA from a PHI patient with mitochondrial AGT (mAGT). This identified three point mutations that cause amino acid substitutions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
180
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(183 citation statements)
references
References 40 publications
3
180
0
Order By: Relevance
“…One such example is provided in the medical condition known as primary hyperoxaluria type 1. About 40% of the cases of primary hyperoxaluria type 1 are caused by mistargeting of the enzyme alanine-glyoxylate aminotransferase from peroxisomes to mitochondria as a result of at least two mutations (33). Wild-type alanine-glyoxylate aminotransferase forms a stable homodimer in the cell (33) with a cryptic N-terminal mitochondrial targeting sequence and a functional C-terminal nonconsensus type 1 peroxisomal targeting sequence (34).…”
Section: Discussionmentioning
confidence: 99%
“…One such example is provided in the medical condition known as primary hyperoxaluria type 1. About 40% of the cases of primary hyperoxaluria type 1 are caused by mistargeting of the enzyme alanine-glyoxylate aminotransferase from peroxisomes to mitochondria as a result of at least two mutations (33). Wild-type alanine-glyoxylate aminotransferase forms a stable homodimer in the cell (33) with a cryptic N-terminal mitochondrial targeting sequence and a functional C-terminal nonconsensus type 1 peroxisomal targeting sequence (34).…”
Section: Discussionmentioning
confidence: 99%
“…Val 326 3 Ile segregates with a variant called the minor (African) AGXT allele (43). Although the functional effects of the two PTS1A polymorphisms have not been well characterized, it is known that Ile 340 3 Met can partially counteract the untoward effects of the Pro 11 3 Leu polymorphism, which include partial mistargeting, slowing down dimerization, and decreasing specific catalytic activity (3,44). In some of the mammals discussed in this report (i.e.…”
Section: Cell Context Dependence Of the Interaction Between Humanmentioning
confidence: 99%
“…AGT is normally peroxisomal in human liver, but in a subset of primary hyperoxaluria type 1 patients it is mistargeted to mitochondria (2). Although the molecular basis of the peroxisome-to-mitochondrion mistargeting of AGT in primary hyperoxaluria type 1 has been subjected to extensive investigation (3)(4)(5)(6), its normal targeting to peroxisomes has received much less attention (7,8).…”
mentioning
confidence: 99%
“…1 Cases have also been identified in subjects suffering from HIV, early cytomegalovirus (CMV) retinitis, and systemic herpes simplex virus (HSV) infection. 2,3 Case report A 37-year-old man with HIV and CMV þ, after 9 weeks of treatment with highly active antiretroviral therapy (HAART) for acute retinal necrosis in OS, was referred for a mild visual acuity (VA) loss in OD (from 20/20 to 20/25). At fundus examination, he presented a perivascular creamy sheathing of retinal veins in the whole vascular net (Figure 1a1Àa2).…”
Section: Discussionmentioning
confidence: 99%
“…2 Eye involvement in primary hyperoxaluria consists of calcium oxalate deposits at the level of the retinal pigment epithelium (RPE) with surrounding areas of hypertrophic and hyperplastic RPE. 1,3 Some authors reported on unusual intraretinal distribution of oxalate deposits, apparently sparing the RPE (studies carried out on ocular tissues obtained at autopsy).…”
mentioning
confidence: 99%